KONSEP ERGONOMIK K3 UNTUK MENINGKATKAN EFEKTIVITAS DAN PRODUKTIVITAS KERJA DI PT. APL - ibnu, freddy dwi; Sudewo (Universitas Pamulang, 2025)
PT APL is a company engaged in the distribution of medical equipment and medicines, with a finance division. Financial data is processed in the operational area. Computers are used in all activities to run business operations. The purpose of this study is to analyze the relationship between ergonomic positions and work posture using the Rapid Office Strain Assessment (ROSA) method in relation to musculoskeletal disorder (MSD) complaints among employees of PT APL. This study shows that at PT APL Semarang, there are four main factors contributing to inadequate workplace ergonomics, namely humans, machines, materials, and methods. The ROSA assessment results revealed that 76.92% of employees are at high risk of musculoskeletal disorders, mainly influenced by the use of non-ergonomic chairs. Employees often lack awareness regarding proper chair height adjustment, leading to poor sitting posture. In addition, improper monitor placement and incorrect positioning of mouse and keyboard use also contribute to the high risk. Awareness of workplace facility adjustments and education on ergonomics in the workplace are crucial to reducing health-related risks for employees. Keywords: Ergonomics, Musculoskeletal Disorders (MSDs), Work Posture, Employees, Risk, Rapid Office Strain Assessment (ROSA), and PT APL.